THE RELATIONSHIP BETWEEN SPIRITUAL INTELLEGENCE AND LEARNING INTEREST OF GRADE VIII STUDENTS OF SMP NEGERI 2 MERANTI IN THE 2022/2023 ACADEMIC YEAR - Juita Sembiring (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
This study aims to determine the RELATIONSHIP BETWEEN SPIRITUAL INTELLEGENCE AND LEARNING INTEREST OF GRADE VIII STUDENTS OF SMP NEGERI 2 MERANTI 2022/2023 ACADEMIC YEAR. This type of research is descriptive correlational research. The population in this study were all grade VII students of SMP NEGERI 2 MERANTI as many as 30 people, because the population was small, which was only 30 people, the entire population became the research sample, namely 30 people with a sampling technique. The data collection instrument for variable X was a questionnaire totaling 15 with 4 options which were first tested to determine its validity and reliability. While the variable Y instrument was the documentation of the student grade list (DKN) at the school. The results of the analysis requirements for the normality test of Spiritual Intelligence data were normally distributed with the calculation results obtained (22.33 <43.77) and student learning interest was normally distributed with the calculation results (18.85 <43.77). The results of the linearity test of the data on the Relationship between Spiritual Intelligence and Students' Interest in Learning are linear with the equation Y = 22.77 + 1.22x being linear. The results of the correlation test obtained were 0.453 consulted with r with a significance level of 5% with the number of respondents being 30 people obtained because (0.453 > 0.361) this indicates that there is a Relationship between Spiritual Intelligence and Students' Interest in Learning in Class VIII of SMP NEGERI 2 MERANTI Academic Year 2022/2023. Furthermore, to test the significance of the correlation, it was carried out using the statistical test formula (test